2021
DOI: 10.1101/2021.12.20.473587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Porphyrin in prebiotic catalysis: Ascertaining a route for the emergence of early metalloporphyrins

Abstract: Metal ions are known to catalyze certain prebiotic reactions. However, the transition from metal ions to extant metalloenzymes remains unclear. Porphyrins are found ubiquitously in the catalytic core of many ancient metalloenzymes. In this study, we evaluated the influence of porphyrin-based organic scaffold, on the catalysis, emergence and putative molecular evolution of prebiotic metalloporphyrins. We studied the effect of porphyrins on the transition metal ion-mediated oxidation of hydroquinone (HQ). We rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…In numerous examples it has been clearly showcased that different types of heme and their organic precursors can be synthesized under prebiotically plausible conditions. These conditions include (i) different Miller–Urey type experimental settings (Szutka, 1964; Hodgson and Baker, 1967; Hodgson and Ponnamperuma, 1968; Simionescu et al ., 1978; Meierhenrich et al ., 2005; Lindsey et al ., 2009); (ii) conditions that mimic primordial volcanic islands (Fox and Strasdeit, 2013) or hydrothermal vents (Seitz et al ., 2021); and (iii) other conditions as well (Soares et al ., 2013; Alexy et al ., 2015; Deans et al ., 2016; Taniguchi et al ., 2016; Pleyer et al ., 2018; Dagar et al ., 2022).…”
Section: The Possible Presence Of Hemes In Prebiotic Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous examples it has been clearly showcased that different types of heme and their organic precursors can be synthesized under prebiotically plausible conditions. These conditions include (i) different Miller–Urey type experimental settings (Szutka, 1964; Hodgson and Baker, 1967; Hodgson and Ponnamperuma, 1968; Simionescu et al ., 1978; Meierhenrich et al ., 2005; Lindsey et al ., 2009); (ii) conditions that mimic primordial volcanic islands (Fox and Strasdeit, 2013) or hydrothermal vents (Seitz et al ., 2021); and (iii) other conditions as well (Soares et al ., 2013; Alexy et al ., 2015; Deans et al ., 2016; Taniguchi et al ., 2016; Pleyer et al ., 2018; Dagar et al ., 2022).…”
Section: The Possible Presence Of Hemes In Prebiotic Timesmentioning
confidence: 99%
“…As a reaction product, a mixture of different porphyrins is obtained. Metalation of the porphyrins occurs in a third step (Pleyer et al ., 2018; Dagar et al ., 2022) or alternatively, metal salts are present during the synthesis with the metal ion coordinating to the forming porphyrins. In the latter case, it has been shown that the presence of metal ions significantly increased the yield of pyrroles (Seitz et al ., 2021) and porphyrins (Simionescu et al ., 1978) as compared to metal-free reactions.…”
Section: The Possible Presence Of Hemes In Prebiotic Timesmentioning
confidence: 99%